Дослідження системи Cu2S – CoS – TiS2 при 870 К - Татарин, Н. A.; Бирук, Г. М.; Кормош, Ж. О.; Парасюк, О. В.; Піскач, Л. В.; Tataryn, N. A.; Byruk, G. M.; Kormosh, Zh. O.; Parasіuk, O. V.; Piskach, L. V. (Волинський національний університет імені Лесі Українки, 2011)
870 K. У цій системі виявлено нові тернарний та тетрарний сульфіди, що кристалізуються в кубічній сингонії: просторовій групі Fd-3m, стр. типі MgAl2O4 з параметрами елементарної комірки для Cu2CoTi3S8 – а = 0,99003 нм і для Cu2Ti4S9 – а = 1,00034 нм, утворюючи між собою необмежений ряд твердих розчинів. Ключові слова: халькогеніди, ізотермічний переріз, кристалічна структура, рентгенівська дифракція. Isothermal section of the Cu2S – CoS – TiS2 system at 870 K was investigated by X-ray phase analysis results. A new ternary and a quaternary sulfide were discovered in this system. They both crystallize in the cubic symmetry, space group Fd-3m, MgAl2O4 structure type, with the unit cell parameters а = 0,99003 nm for Cu2CoTi3S8 and а = 1,00034 nm for Cu2Ti4S9. The compounds form a continuous solid solution series. Key words: chalcogenides; isothermal section; crystal structure; X-ray powder diffraction.
Investigation of the Cu2S − CoS – TiS2 System at 870 K.
Keywords: халькогеніди; ізотермічний переріз; кристалічна структура; рентгенівська дифракція; chalcogenides; isothermal section; crystal structure; X-ray powder diffraction